Analisis Pinsip Kerja Sama dalam Acara Komedi Stand Up Comedy Season 2 - Putri Argita Prasasti; Arzha Ali Rahmat; Puti Sekar Arginingrum; Yanuar Bagas Arwansyah; Asep Purwo Yudi Utomo (Pusat Riset dan Inovasi Nasional, 2022)
In a conversation, it definitely requires a principle of cooperation, so that the speech partner can understand what the speaker is saying. However, often between speakers or their interlocutors violate conversations which can result in a violation of the principle of cooperation. So that this research was made with the aim of knowing the implementation and violation of the cooperative principle contained in the Stand-Up Comedy Season 2 conversation. note in the process of data collection stage. As a result, the researcher found several utterances that implemented or violated the cooperative principle in a conversation on the Stand-Up Comedy Season 2. The results were in the form of three conversations which were maxims of quality (one utterance did not violate the maxim of quality and two utterances violated the maxim of quality). Two conversations of maxim of quantity (one utterance violates and one utterance does not violate maxim of quantity). Three conversations are maxims of relevance (two utterances do not violate and one utterance violates maxims of relevance). Conversation, Cooperation Principles, Implicature, Pragmatics, and Stand Up Comedy.